أثر القرار التمويلي في الربحية "دراسة تطبيقية على شركات صناعة النسيج في سورية" - العمار, رضوان; غيا, دانيا (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يهدف هذا البحث إلى دراسة أثر القرار التمويلي (Financial Decision) على الربحية في شركات الصناعة النسيجية في الساحل السوري خلال الفترة (2000-2016) وهي ثلاث شركات غير مدرجة في سوق دمشق للأوراق المالية. وقد تم قياس القرار التمويلي بكل من نسبة الديون الإجمالية إلى إجمالي الأصول (Total Debt to Total assets) (TD)، والربحية بكل من معدل العائد على الأصول (Return on Assets) (ROA) ومعدل العائد على حقوق الملكية (Return on Equity) (ROE) ومعدل العائد على رأس المال (Return on Capital) (ROC). وقد تم الاعتماد على سلسلة من البيانات المالية السنوية للشركات الثلاث خلال الفترة المدروسة (Panel Data). وبهدف تقدير نماذج الدراسة تم استخدام اختبار جذر الوحدة لاختبار استقراريه المتغيرات المدروسة. وبعد التأكد من استقراريتها تم تقدير نماذج الانحدار باستخدام طريقة المربعات الصغرى العادية. وقد توصلت الدراسة إلى نتائج عديدة أهمها أن للديون أثر سلبي في الربحية على اختلاف النسب المستخدمة في قياس كل من الديون والربحية. The purpose of this research is to study the impact of the financing decision (FD) on profitability in the textile industry companies in the Syrian coast during the period (2000-2016), which are three companies not listed on the Damascus Stock Exchange. The financing decision was measured in terms of ratio of total debt to total assets (TD), Profitability was measured by return on assets (ROA), return on equity (ROE) and return on capital (ROC). A series of annual financial statements of the three companies were used during the period reviewed (Panel Data). In order to estimate the models of the study, the unit root test was applied to test the stability of the studied variables. After confirming their stability, the regression models were estimated using the normal lower squares method. The study reached several results, the most important of which is that the debt has a negative impact on profitability in different ratios used to measure both debt and profitability.